Plan de gestión integral de residuos sólidos para la Dirección General Marítima (Dimar), distrito especial de Buenaventura, Valle del Cauca-Colombia (2019)
This investigative document deals with the design of a Comprehensive Solid Waste Management Plan for the three land units of the DIMAR (Maritime General Directorate) Regional-Buenaventura institution, to comply with current regulations (Decree 1077/2015). In order to contribute positively to the environmental problems, present in the region regarding the proper management of solid waste. To carry out the above, a series of activities such as characterization were carried out, where the sampling units, total number of samples and evaluative parameters were defined. An initial diagnosis was also made, to find programs and / or strategies in relation to the proper management of solid waste and facilitate its use. In order to guarantee an optimal life cycle for the three land units of the Institution